A method for simulating the corrosion of composite coatings

By comprehensively using salt spray test method, humidity and heat test method and electrochemical corrosion test method, the corrosion resistance of the composite coating is evaluated and the preparation and optimization is carried out, the problem of single dimensions of the coating performance simulation experimental method in the existing technology is solved, and the problem of achieving the Accurate evaluation and optimization of coating properties.

CN118730875BActive Publication Date: 2025-02-11GANSU ELECTRIC POWER DESIGN INST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410948061.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-16
Publication Date
2025-02-11
Estimated Expiration
2044-07-16

AI Technical Summary

Technical Problem

The existing coating performance simulation experimental methods have a single dimension and cannot obtain accurate coating performance data, resulting in a deviation in experimental results.

Method used

The corrosion resistance performance index of the coating was comprehensively evaluated by salt spray test method, moisture and heat test method and electrochemical corrosion test method, and prepared and optimized.

Benefits of technology

The corrosion resistance and adhesion of the composite coating is improved, and its wear resistance and durability are enhanced, ensuring the corrosion resistance and performance accuracy of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118730875B_ABST
    Figure CN118730875B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coating material experiments, and specifically discloses a corrosion simulation experimental method for a composite coating. The method comprises: composite coating preparation, corrosion resistance performance index evaluation and corrosion performance optimization. Firstly, the composite coating is prepared, and corrosion experimental operations are performed on the composite coating respectively by using a salt spray test method, a wet heat test method and an electrochemical corrosion test method, and the corrosion resistance performance index of the composite coating is comprehensively evaluated, so that the corrosion performance of the composite coating is prepared and optimized, the corrosion resistance of the composite coating and the adhesion between the composite coating and the substrate are improved, and the optimized composite coating has higher hardness and wear resistance, can resist wear and scratches, and effectively enhances the corrosion resistance stability of the composite coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating material experiments, in particular to a composite coating erosion simulation experiment method. Background Art

[0002] Currently, when conducting corrosion tests on coatings, the requirements for the test chambers required for the experiments are relatively high. That is, most test chambers will be destroyed when conducting cavitation tests under corrosive media, so that the experimental results may be affected by a variety of uncertain factors. The instability of this technology may cause uneven or unstable coating performance. At the same time, even if the coating exhibits good performance in the experiment, in actual applications, the composite coating may be affected by more complex and changeable environmental factors, resulting in performance degradation or failure.

[0003] For example, the invention patent with announcement number CN116589907B, the above application involves the technical field of building protective materials, and specifically discloses a durable concrete surface protective coating; the durable concrete surface protective coating includes an epoxy sealing primer layer, an epoxy micaceous iron intermediate paint layer and a fluorocarbon topcoat layer; the epoxy sealing primer is composed of components A1 and B1; the A1 component includes: dispersant, defoamer, iron oxide red, epoxy resin, xylene, amino-modified fullerene; the B1 component includes: phenolic amine curing agent, phenolic modified amine, xylene; the epoxy micaceous iron intermediate paint is composed of components A2 and B2; the A2 component includes: epoxy resin, micaceous iron oxide, aluminum powder, polyvinyl alcohol / sodium carboxymethyl cellulose cross-linked microspheres, butanol, dispersant, phenyl salicylate, dihydroxyethyl dodecyl trimethyl ammonium chloride modified montmorillonite KSF; the B2 component includes: phenolic modified amine, butanol. The durable concrete surface protective coating of this application has excellent weather resistance and mechanical properties.

[0004] For example, the invention patent with announcement number CN104693967B relates to a protective agent for improving the durability and apparent quality permeability of hydraulic concrete, characterized in that the protective agent comprises a base surface correction material interface agent, a color difference adjuster, a waterproof primer, and a topcoat; the superior effect of the protective agent described in the above application is that through experimental research and engineering practice, the protective agent described in the above application can effectively prevent chloride ions, acid, and alkali chemical media from penetrating into concrete after use, prevent corrosive molecules from damaging concrete and its internal steel bars, and delay damage to concrete caused by light, ultraviolet radiation, alternating high and low temperatures, and alternating dry and wet conditions.

[0005] Combined with the above technical solutions, it is found that as the application fields of coatings gradually expand, it is necessary to organize more safe, effective and reliable coating performance simulation experiment technical solutions. However, when conducting analytical experiments on the performance of coatings, most technical solutions use relatively single-dimensional experimental methods, which will make it impossible to obtain accurate performance data of the coatings, making it difficult for the experimental results of the coatings to meet expectations, resulting in deviations in the coating performance simulation experiments. Therefore, it is necessary to have an accurate and reliable coating performance simulation experiment technical solution. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a composite coating corrosion simulation test method, which can effectively solve the problems involved in the above-mentioned background technology.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: a composite coating corrosion simulation test method, including: composite coating preparation: obtaining a composite coating material to be tested, preparing a paint layer for the composite coating material to be tested, and recording the prepared composite coating material to be tested as a composite coating; corrosion resistance performance index evaluation: using a salt spray test method, a wet heat test method and an electrochemical corrosion test method to perform corrosion test operations on the composite coating respectively, and comprehensively evaluating the corrosion resistance performance index of the composite coating; corrosion performance optimization: comparing the corrosion resistance performance index of the composite coating with a preset corrosion resistance performance threshold, so as to optimize the corrosion performance of the composite coating.

[0008] As a further method, the erosion performance of the composite coating is prepared and optimized, and the specific analysis process is: comparing the erosion resistance index of the composite coating with a preset erosion resistance threshold value, if the erosion resistance index of the composite coating is greater than or equal to the erosion resistance threshold value, there is no need to prepare and optimize the erosion performance of the composite coating; if the erosion resistance index of the composite coating is less than the erosion resistance threshold value, then obtaining the composite coating material to be tested again, and preparing a paint layer for the composite coating material to be tested, recording the prepared composite coating material to be tested as a composite coating, and performing corrosive experimental operations on the composite coating again until the erosion resistance index of the composite coating is greater than or equal to the preset erosion resistance threshold value, thereby completing the preparation optimization of the erosion performance of the composite coating.

[0009] As a further method, the corrosion resistance index of the composite coating is obtained by performing corrosion experiments on the composite coating through salt spray test, wet heat test and electrochemical corrosion test, respectively, to obtain the corrosion degree of the composite coating in the salt spray test, the corrosion degree of the composite coating in the wet heat test and the corrosion degree of the composite coating in the electrochemical corrosion test, and comprehensively analyzing the corrosion resistance index of the composite coating. The specific analysis formula is:

[0010]

[0011] in It is represented as the corrosion resistance index of the composite coating, Y is represented as the corrosion degree of the composite coating in the salt spray test, S is represented as the corrosion degree of the composite coating in the wet heat test, F is represented as the corrosion degree of the composite coating in the electrochemical corrosion test, y1 is represented as the weight factor corresponding to the corrosion degree of the composite coating in the salt spray test predefined in the corrosion experiment information library, y2 is represented as the weight factor corresponding to the corrosion degree of the composite coating in the wet heat test predefined in the corrosion experiment information library, and y3 is represented as the weight factor corresponding to the corrosion degree of the composite coating in the electrochemical corrosion predefined in the corrosion experiment information library.

[0012] As a further method, the salt spray test method, specific materials include a salt spray test box, edible salt, distilled water, and ethanol; by performing a salt spray test on the composite coating, salt spray test data is obtained, and the salt spray test composite coating corrosion degree is evaluated.

[0013] As a further method, the wet heat test method uses a high and low temperature wet heat test chamber as a specific material; by performing the wet heat test on the composite coating, a wet heat test data set is obtained, thereby evaluating the corrosion degree of the composite coating in the wet heat test.

[0014] As a further method, the electrochemical corrosion test method, the specific materials include electrolyte, saturated calomel electrode, electrolytic cell; the composite coating is used as a working electrode, the saturated calomel electrode is used as a reference electrode, they are placed together in the electrolytic cell, and the electrolyte is added to form an electrochemical cell; by performing an electrochemical corrosion test on the composite coating, electrochemical data of electrochemical corrosion is obtained, and the erosion degree of the electrochemical corrosion composite coating is evaluated.

[0015] As a further method, the composite coating material to be tested is subjected to paint layer preparation, and the specific analysis process is as follows: according to the composite coating material to be tested, specifically including isobutyl triethoxy silane, water, cement, machine-made sand, rubber powder, nano silicon dioxide, admixture and sodium laurate; the composite coating material is subjected to paint layer preparation, wherein the paint layer preparation includes composite coating primer preparation, composite coating intermediate paint preparation and composite coating topcoat preparation; through the composite coating primer preparation, specifically isobutyl triethoxy silane is added to water, wherein the ratio of the volume of isobutyl triethoxy silane to the volume of water is the same as the preset ratio, thereby obtaining a composite coating; A layer of primer; a composite coating intermediate paint is prepared by mixing cement, machine-made sand, rubber powder and nano-silicon dioxide according to a preset ratio and stirring for a first specified time to obtain a dry material mixture, adding water and an admixture to the dry material mixture and stirring for a second specified time to obtain a composite coating intermediate paint; a composite coating topcoat is prepared by adding sodium laurate to water and stirring for a third specified time to obtain a composite coating topcoat; according to the composite coating primer, the composite coating intermediate paint and the composite coating topcoat, the paint layer of the composite coating material is prepared, and the prepared composite coating material to be tested is recorded as a composite coating.

[0016] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:

[0017] (1) The present invention provides a method for simulating the corrosion of a composite coating. First, a composite coating is prepared. A salt spray test method, a wet heat test method, and an electrochemical corrosion test method are used to perform corrosion test operations on the composite coating respectively. The corrosion resistance index of the composite coating is comprehensively evaluated, so that the corrosion performance of the composite coating is prepared and optimized, and the corrosion resistance of the composite coating and the adhesion between the composite coating and the substrate are improved. The optimized composite coating has higher hardness and wear resistance, can resist wear and scratches, and effectively enhances the corrosion resistance stability of the composite coating.

[0018] (2) The present invention prepares a paint layer on the composite coating material to be tested, and efficiently prepares the composite coating material to be tested, which is beneficial to improving the friction resistance, durability and corrosion resistance of the composite coating.

[0019] (3) The present invention uses salt spray test method, wet heat test method and electrochemical corrosion test method to perform corrosive test operations on the composite coating respectively. Through a variety of different experimental methods, the anti-corrosion performance and corrosion resistance of the composite coating can be comprehensively evaluated, which helps to understand the corrosive performance of the composite coating under different conditions, and comprehensively evaluate the corrosion resistance performance index of the composite coating. It can accurately understand the corrosion resistance of the composite coating in different environments and ensure the corrosion resistance quality of the composite coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0021] Figure 1 It is a schematic diagram of the method flow of the present invention.

[0022] Figure 2 Schematic diagram of the composite coating structure.

[0023] Figure 3 This is a current-potential variation curve diagram involved in the present invention.

[0024] As shown in the attached figure: 1. Composite coating primer; 2. Composite coating intermediate paint; 3. Composite coating topcoat; 4. Connecting straight line; 5. First horizontal straight line. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] Reference Figure 1 As shown, the present invention provides a composite coating corrosion simulation test method, including: composite coating preparation: obtaining a composite coating material to be tested, preparing a paint layer for the composite coating material to be tested, and recording the prepared composite coating material to be tested as a composite coating.

[0027] Specifically, the paint layer of the composite coating material to be tested is prepared, and the specific analysis process is as follows:

[0028] The composite coating materials to be tested specifically include isobutyltriethoxysilane, water, cement, machine-made sand, rubber powder, nano-silicon dioxide, admixtures and sodium laurate. The composite coating materials to be tested are all purchased from the market.

[0029] The machine-made sand is medium sand, the admixture is polycarboxylic acid liquid water reducing agent, the nano silicon dioxide is high-purity nano silicon dioxide with an average particle size of 20 nanometers and a content greater than or equal to 99.9%, and the rubber powder is 5044N type redispersible latex powder.

[0030] The composite coating material is subjected to paint layer preparation, wherein the paint layer preparation includes composite coating primer preparation, composite coating intermediate paint preparation and composite coating topcoat preparation, such as Figure 2As shown, it is a composite coating structure diagram, including a composite coating primer 1, a composite coating intermediate paint 2 and a composite coating topcoat 3.

[0031] The composite coating primer is prepared by adding isobutyl triethoxy silane into water, wherein the ratio of the volume of isobutyl triethoxy silane to the volume of water is the same as a preset ratio, thereby obtaining the composite coating primer.

[0032] The specific ratios of the materials involved in the present embodiment will vary with the specific required performance of the composite coating, the use environment, and the substrate, so this embodiment does not make any special restrictions on this.

[0033] The above preset ratios are defined in the erosion experiment information library.

[0034] The data stored in the above-mentioned erosion experiment information library is obtained by fitting based on the statistical test status information of multiple composite coatings. For example, the preset ratio is obtained by preparing different preset configuration ratios for the composite coating material, and fitting the configuration ratio determined by the test personnel to meet the optimal erosion resistance state of the composite coating as the preset ratio for the preparation of the composite coating material. In this way, the values ​​in the erosion experiment information library are obtained, wherein the values ​​may vary due to the quality of the composite coating, the degree of corrosion resistance, and the experimental method. This embodiment does not make any special limitation on this.

[0035] The composite coating intermediate paint is prepared by mixing cement, machine-made sand, rubber powder and nano-silicon dioxide according to a preset ratio and stirring for a first specified time, wherein the stirring time is set to 30 seconds in this embodiment, and its main purpose is to fully and evenly stir the above materials to obtain a dry material mixture; water and admixtures are added to the dry material mixture, and stirred for a second specified time, wherein the stirring time is set to 120 seconds in this embodiment, and its main purpose is to fully and evenly stir the above materials to obtain a composite coating intermediate paint.

[0036] The composite coating topcoat is prepared by adding sodium laurate into water and stirring for a third specified time, wherein the stirring for the specified time is set to 60s in this embodiment, and its main purpose is to fully and evenly stir the above materials to obtain the composite coating topcoat.

[0037] The paint layer of the composite coating material is prepared according to the composite coating primer, the composite coating intermediate paint and the composite coating topcoat, and the prepared composite coating material to be tested is recorded as a composite coating.

[0038] Evaluation of corrosion resistance performance index: The salt spray test method, the wet heat test method and the electrochemical corrosion test method are used to carry out corrosion experiments on the composite coating, and the corrosion resistance performance index of the composite coating is comprehensively evaluated.

[0039] Furthermore, the salt spray test method specifically includes materials such as a salt spray test box, edible salt, distilled water, and ethanol.

[0040] The specific process of the above-mentioned salt spray test method is: edible salt is added to distilled water for dissolution to prepare a saline solution, and a pH meter is used to detect the pH value of the saline solution to ensure that the pH value of the saline solution is between 6.5 and 7.2.

[0041] Use ethanol to clean and dry the composite coating, and place the cleaned and dried composite coating in a salt spray test chamber. The composite coating should be placed in a position that prevents them from being directly sprayed by the sprayer; add saline solution into the water inlet of the salt spray test chamber, start the salt spray test chamber, allow a salt spray environment to form in the chamber, and start the experiment. Set the required time according to the test requirements, conduct the salt spray test, and record the salt spray test data.

[0042] By subjecting the composite coating to a salt spray test, salt spray test data is obtained, and the corrosion degree of the composite coating in the salt spray test is evaluated.

[0043] Specifically, the salt spray test composite coating corrosion degree, the specific analysis process is:

[0044] According to the salt spray test data, the initial pH value in the salt spray test box, the pH value at the test termination time point, and the number of bubbles on the composite coating surface are extracted, wherein the test termination time point is obtained by dividing the test cycle into various test time points, and the test cycle is determined by the test personnel based on the test requirements, the corrosion state of the composite coating, the experimental environment and other factors. The pH values ​​involved in this embodiment can be obtained by acid-base test paper; the number of bubbles on the composite coating surface can be obtained by counting under a microscope.

[0045] The initial pH value in the salt spray test chamber is subtracted from the pH value of the salt spray test chamber at the end time of the test to obtain the pH change value of the salt spray test chamber during the test period.

[0046] The initial salt spray concentration in the salt spray test area and the salt spray concentration in the salt spray test area at the test termination time point are obtained, wherein the salt spray concentration can be obtained by detection by a salt spray test machine, and ratio processing is performed to obtain the environmental salt spray leakage degree of the salt spray test area during the test period, which is multiplied by the correction factor corresponding to the environmental salt spray leakage degree preset in the corrosion experiment information library to obtain the salt spray test environmental salt spray leakage impact index.

[0047] The correction factor corresponding to the above-mentioned environmental salt spray leakage degree can be obtained by fitting the historical salt solution concentration, the historical salt spray deposition, and the historical test temperature to obtain the fitting curve corresponding to the environmental salt spray leakage degree, and the salt solution concentration, salt spray deposition, and test temperature in the real-time salt spray test area are brought into the fitting curve corresponding to the environmental salt spray leakage degree, thereby obtaining the correction factor corresponding to the environmental salt spray leakage degree in this embodiment, and the value range in this embodiment is (0, 1).

[0048] The acid-base change value of the salt spray test box during the test period is compared with the acid-base reference change value preset in the corrosion test information library to obtain the acid-base change index of the salt spray test box.

[0049] The number of bubbles on the composite coating surface is multiplied by the influence factor corresponding to a single bubble preset in the erosion experiment information library to obtain the erosion influence index of the composite coating surface.

[0050] The influencing factor corresponding to the above-mentioned single bubble can be obtained by fitting the historical data of the composite coating, including the tension, pressure and activity level of the composite coating surface, to obtain a fitting curve corresponding to the single bubble, and the real-time tension, pressure and activity level of the composite coating surface are brought into the fitting curve corresponding to the single bubble to obtain the influencing factor corresponding to the single bubble. At the same time, the value range in this embodiment is (0, 1).

[0051] The salt spray leakage impact index of the salt spray test environment, the acid-base change index of the salt spray test box and the corrosion impact index of the composite coating surface are added together to obtain the corrosion degree of the composite coating in the salt spray test.

[0052] There is an inverse proportional relationship between the environmental salt spray leakage rate in the above-mentioned salt spray test area during the test period and the corrosion rate of the composite coating in the salt spray test. There is a direct proportional relationship between the pH change value of the salt spray test box during the test period and the number of bubbles on the surface of the composite coating and the corrosion rate of the composite coating in the salt spray test.

[0053] Furthermore, the specific material of the humidity and heat test method is a high and low temperature humidity and heat test box.

[0054] The specific steps of the above-mentioned humidity and heat test method are as follows: first, the composite coating is cleaned and dried, and the cleaned and dried composite coating is placed in a high and low temperature humidity and heat test box. In this embodiment, the initial temperature in the box is set to 23 degrees Celsius and the initial relative humidity is 50%. The test box is subjected to experimental operations of heating and humidification, high temperature and high humidity maintenance, high temperature and high humidity continuation, cooling and high humidity maintenance, and low temperature and high humidity continuation. The experimental operations of high temperature and high humidity maintenance, high temperature and high humidity continuation, cooling and high humidity maintenance, and low temperature and high humidity continuation are performed in a cycle, and the humidity and heat test operations are recorded in real time to obtain a data set of the humidity and heat test, thereby evaluating the erosion degree of the composite coating in the humidity and heat test.

[0055] In this embodiment, the temperature-humidity changes of the above experimental operation are shown in Table 1:

[0056] Table 1 Temperature-humidity change comparison table

[0057]

[0058] In this embodiment, according to the table comparing the changes in temperature and humidity, the composite coating is subjected to dual changes in temperature and humidity in the wet heat test method, and the erosion of the composite coating under different temperatures and humidities is observed, including testing the stability and reliability of the composite coating in a heated and humidified environment, the performance and durability in a high temperature and high humidity environment, the long-term stability and reliability in such an extreme environment as high temperature and high humidity, and the cold resistance and moisture resistance in a cooled and high humidity environment, so as to determine the erosion degree of the composite coating in the wet heat test.

[0059] By carrying out a wet heat test on the composite coating, a data set of the wet heat test is obtained, thereby evaluating the corrosion degree of the composite coating in the wet heat test.

[0060] Specifically, the wet heat test composite coating erosion degree, the specific analysis process is:

[0061] According to the data set of the wet heat test, the peeling area of ​​the composite coating at the wet heat termination time point, the total area of ​​the composite coating, the initial coating thickness of the composite coating and the coating thickness of the composite coating at the wet heat termination time point were extracted.

[0062] The above-mentioned damp heat termination time point is obtained by dividing the damp heat cycle into various damp heat time points. The determination of the damp heat cycle is determined by the testing personnel based on comprehensive judgment of factors such as test requirements, corrosion status of the composite coating, and experimental environment; the peeling area and the total area can be obtained through the area formula; the coating thickness can be measured by a ruler.

[0063] The erosion and spalling ratio of the composite coating was obtained by performing a ratio processing on the spalling area of ​​the composite coating at the wet heat termination time point and the total area of ​​the composite coating.

[0064] The initial coating thickness of the composite coating and the coating thickness of the composite coating at the end time point of wet heat are subjected to difference processing to obtain the coating thickness difference of the composite coating during the wet heat cycle, and the difference is multiplied by the influence factor corresponding to the coating thickness difference preset in the corrosion experiment information library. The obtained value is recorded as the corrosion thickness influence value of the composite coating.

[0065] The influencing factor corresponding to the above-mentioned coating thickness difference can be fitted by the historical substrate surface roughness, the historical composite coating viscosity, and the historical measuring instrument error value to obtain a fitting curve corresponding to the coating thickness difference, and the real-time substrate surface roughness, composite coating viscosity, and measuring instrument error value are brought into the fitting curve to obtain the influencing factor corresponding to the coating thickness difference in this embodiment, and the value range in this embodiment is (0, 1).

[0066] The erosion and spalling ratio of the composite coating is compared with the erosion and spalling limit ratio defined in the erosion experiment information database to obtain the erosion and spalling index of the composite coating.

[0067] The erosion thickness influence value of the composite coating and the erosion spalling index of the composite coating are added together to obtain the erosion degree of the composite coating in the wet heat test.

[0068] Furthermore, the electrochemical corrosion testing method specifically includes materials including an electrolyte, a saturated calomel electrode, and an electrolytic cell.

[0069] The composite coating is used as a working electrode, and a saturated calomel electrode is used as a reference electrode. The two electrodes are placed together in an electrolytic cell, and an electrolyte is added to form an electrochemical cell.

[0070] The specific steps of the above-mentioned electrochemical corrosion test method are: immerse the working electrode in the electrolyte for one hour to make it reach a stable state, and then apply current to the electrochemical cell, construct a current-potential change curve in the electrochemical cell according to the current change in the electrochemical cell, record the state of the working electrode in the electrochemical cell, obtain the electrochemical data of electrochemical corrosion, and evaluate the erosion degree of the electrochemical corrosion composite coating.

[0071] By conducting an electrochemical corrosion test on the composite coating, electrochemical data of electrochemical corrosion is obtained and the erosion degree of the electrochemical corrosion composite coating is evaluated.

[0072] Specifically, the erosion degree of the electrochemical corrosion composite coating is analyzed in the following process:

[0073] According to the electrochemical data of electrochemical corrosion, the current and potential of the electrochemical cell at each corrosion time point are extracted, and the current-potential change curve in the electrochemical cell is constructed, from which the maximum polarization resistance of the electrochemical cell during the corrosion cycle is extracted.

[0074] The above corrosion time points are obtained by dividing the corrosion cycle into various corrosion time points. The corrosion cycle is determined by the inspection personnel based on comprehensive judgment of factors such as test requirements, corrosion state of the composite coating, and experimental environment; among them, both the current and the potential can be detected by an ammeter.

[0075] According to the current and potential of the electrochemical cell at each corrosion time point, the current-potential change curve in the electrochemical cell is constructed, such as Figure 3 As shown, the horizontal axis of the current-potential variation curve is the current, the unit is ampere, and the vertical axis is the potential, the unit is volt.

[0076] According to the current-potential variation curve, the connecting straight line 4 and the first horizontal straight line 5 of two adjacent current-potential points are located, wherein the minimum angle of intersection between the connecting straight line 4 and the first horizontal straight line 5 is the polarization resistance of the electrochemical cell at each time point corresponding to the current-potential. The polarization resistance of the electrochemical cell at each time point is arranged in ascending order, and the polarization resistance ranked first is recorded as the maximum polarization resistance of the electrochemical cell during the corrosion cycle.

[0077] Obtain the adhesion between the composite coating and the substrate at the corrosion termination time point, the environmental initial temperature of the electrochemical corrosion test area at the corrosion start time point, and the environmental temperature of the electrochemical corrosion test area at the corrosion termination time point, wherein the adhesion can be obtained by a tensile sensor and the temperature can be obtained by a thermometer.

[0078] The defined adhesion and reference temperature differences are extracted from the corrosion test database.

[0079] The erosion degree of the electrochemical corrosion composite coating is comprehensively analyzed. In this embodiment, it is obtained by comprehensively analyzing the maximum polarization resistance of the electrochemical cell during the corrosion cycle, the adhesion between the composite coating and the substrate at the corrosion termination time point, and the ambient temperature difference in the electrochemical corrosion test area. This is used to determine the erosion degree of the electrochemical corrosion composite coating. In this embodiment, a more accurate calculation method is used to obtain it. The specific expression is:

[0080]

[0081] Where ΔW = (CW-HW)*b1;

[0082] Wherein F represents the erosion degree of the electrochemical corrosion composite coating. In this embodiment, when the polarization resistance of the electrochemical cell is large, it may cause the contact resistance between the composite coating and the substrate to increase, making the charge exchange between the coating and the substrate difficult, affecting the electrochemical process, reducing the erosion degree of the electrochemical corrosion composite coating, and increasing the adhesion between the composite coating and the substrate. At the same time, the key to the electrochemical corrosion experiment is to maintain temperature stability. If the ambient temperature difference in the electrochemical corrosion test area is large, it will affect the determination of the erosion degree of the electrochemical corrosion composite coating. A simplified approach is adopted for this expression to reduce the erosion degree of the composite coating during the electrochemical corrosion test.

[0083] Z represents the maximum polarization resistance of the electrochemical cell during the corrosion cycle, which refers to the maximum ratio of the current to the potential of the electrochemical cell during the corrosion cycle.

[0084] N represents the adhesion between the composite coating and the substrate at the corrosion termination time point, which refers to the mutual attraction between the contact part of the composite coating and the substrate.

[0085] N ′ Expressed as limiting adhesion, it refers to the minimum value of adhesion.

[0086] ΔW is represented by the ambient temperature difference of the electrochemical corrosion test area, which refers to the difference between the initial ambient temperature of the electrochemical corrosion test area at the corrosion start time point and the ambient temperature of the electrochemical corrosion test area at the corrosion end time point.

[0087] W ′ Expressed as reference temperature difference, it refers to the standard value of temperature difference.

[0088] In this embodiment, the ambient temperature difference of the electrochemical corrosion test area is set to 13 degrees Celsius, and the reference temperature difference is set to 10 degrees Celsius. Then, in this expression: The result of the partial calculation is 0.3.

[0089] a1 represents the influence factor corresponding to the unit value of polarization resistance defined in the corrosion experiment information library, and a2 represents the influence factor corresponding to the unit value of electrochemical corrosion composite coating corrosion degree predefined in the corrosion experiment information library.

[0090] The influencing factor corresponding to the unit value of the polarization resistance preset in the above-mentioned corrosion experiment information library can be obtained by fitting the fitting curve corresponding to the polarization resistance through the historical electrolyte concentration, current density, and external electric field strength, and the fitting curve corresponding to the polarization resistance is brought into the fitting curve according to the real-time electrolyte concentration, current density, and external electric field strength, thereby obtaining the influencing factor corresponding to the unit value of the polarization resistance in this embodiment, and the value range in this embodiment is (0, 1); the influencing factor corresponding to the unit value of the erosion degree of the electrochemical corrosion composite coating can be obtained by fitting the fitting curve of the erosion degree of the electrochemical corrosion composite coating through the historical polarization resistance, historical temperature, and historical adhesion of the composite coating, and the fitting curve of the erosion degree of the electrochemical corrosion composite coating is brought into the fitting curve according to the real-time polarization resistance, temperature, and adhesion, thereby obtaining the influencing factor corresponding to the unit value of the erosion degree of the electrochemical corrosion composite coating in this embodiment, and the value range in this embodiment is (0, 1).

[0091] CW represents the initial temperature of the environment in the electrochemical corrosion test area at the time when corrosion starts, which refers to the temperature value recorded before the electrochemical corrosion experiment starts in the electrochemical corrosion test area.

[0092] HW represents the ambient temperature of the electrochemical corrosion test area at the corrosion termination time point, which refers to the temperature value recorded after the electrochemical corrosion experiment in the electrochemical corrosion test area is completed.

[0093] b1 represents the impact factor corresponding to the temperature difference unit value predefined in the corrosion experiment information library, and e is a natural constant.

[0094] The influencing factor corresponding to the above-mentioned temperature difference unit value is obtained by fitting the temperature difference fitting curve by fitting the longitude, latitude and altitude of the geographical location of the historical experiment, and the temperature difference fitting curve is brought into the longitude, latitude and altitude of the real-time geographical location, thereby obtaining the influencing factor corresponding to the temperature difference unit value in this embodiment, and the value range in this embodiment is (0, 1).

[0095] Furthermore, the corrosion resistance index of the composite coating, in this embodiment, is obtained by comprehensive analysis of the corrosion degree of the composite coating in the salt spray test, the corrosion degree of the composite coating in the wet heat test, and the corrosion degree of the composite coating in the electrochemical corrosion test, so as to determine the corrosion resistance index of the composite coating. In this embodiment, a more accurate calculation method is used to obtain the corrosion resistance index, and the specific analysis formula is:

[0096]

[0097] in It is expressed as the corrosion resistance index of the composite coating. In this embodiment, if the corrosion degree of the composite coating in the salt spray test, the corrosion degree of the composite coating in the wet heat test and the corrosion degree of the composite coating in the electrochemical corrosion test are all significantly higher, then the corrosion resistance of the surface modified composite coating is poor, and its corrosion resistance index is reduced. It is necessary to take necessary measures to optimize the preparation operation of the composite coating to obtain a composite coating with better corrosion resistance. A simplified processing method is used for this expression to improve the corrosion resistance of the composite coating.

[0098] Y represents the corrosion degree of the composite coating in the salt spray test, which is obtained by comprehensive analysis of the initial pH value in the salt spray test chamber, the pH value of the salt spray test chamber at the test termination time point, the initial salt spray concentration in the salt spray test area, the salt spray concentration in the salt spray test area at the test termination time point, and the number of bubbles on the surface of the composite coating.

[0099] S represents the corrosion degree of the composite coating in the wet heat test, which is obtained by comprehensive analysis of the peeling area of ​​the composite coating at the end time of the wet heat test, the total area of ​​the composite coating, the initial coating thickness of the composite coating, and the coating thickness of the composite coating at the end time of the wet heat test.

[0100] F represents the corrosion degree of the electrochemical corrosion composite coating, which is obtained by comprehensive analysis of the maximum polarization resistance of the electrochemical cell during the corrosion cycle, the adhesion between the composite coating and the substrate at the corrosion termination time point, and the ambient temperature difference in the electrochemical corrosion test area.

[0101] y1 represents the weight factor corresponding to the corrosion degree of the composite coating in the salt spray test predefined in the corrosion experiment information library, y2 represents the weight factor corresponding to the corrosion degree of the composite coating in the wet heat test predefined in the corrosion experiment information library, and y3 represents the weight factor corresponding to the corrosion degree of the composite coating in the electrochemical corrosion predefined in the corrosion experiment information library.

[0102] The weight factors corresponding to the corrosion degree of the above-mentioned salt spray test composite coating, the weight factors corresponding to the corrosion degree of the wet heat test composite coating, and the weight factors corresponding to the corrosion degree of the electrochemical corrosion composite coating are all obtained by fitting the historical salt spray test data, the historical wet heat test data set, and the electrochemical data of historical electrochemical corrosion to obtain their respective corresponding fitting curves, and the real-time salt spray test data, the wet heat test data set, and the electrochemical data of electrochemical corrosion are brought into the corresponding fitting curves, thereby obtaining the weight factors corresponding to the corrosion degree of the salt spray test composite coating, the weight factors corresponding to the corrosion degree of the wet heat test composite coating, and the weight factors corresponding to the corrosion degree of the electrochemical corrosion composite coating in this embodiment.

[0103] In this embodiment, the value range of the weight factor corresponding to the corrosion degree of the composite coating in the salt spray test is (0, 1), and the weight factor corresponding to the corrosion degree of the composite coating in the salt spray test is set to 0.55; the value range of the weight factor corresponding to the corrosion degree of the composite coating in the wet heat test is (0, 1), and the weight factor corresponding to the corrosion degree of the composite coating in the wet heat test is set to 0.63; the value range of the weight factor corresponding to the corrosion degree of the composite coating in the electrochemical corrosion test is (0, 1), and the weight factor corresponding to the corrosion degree of the composite coating in the electrochemical corrosion test is set to 0.6.

[0104] In this embodiment, the corrosion resistance performance index of the above composite coating is as shown in Table 2:

[0105] Table 2 Numerical changes between the corrosion resistance index and parameters of the composite coating

[0106]

[0107] In this embodiment, according to the table of the corrosion resistance performance index of the above-mentioned composite coating, it can be learned that with the increase of the corrosion degree of the composite coating in the salt spray test, the corrosion degree of the composite coating in the wet heat test, and the corrosion degree of the composite coating in the electrochemical corrosion test, the corrosion resistance performance index of the composite coating decreases, which means that the composite coating is corroded under these test methods and its corrosion resistance is poor. Therefore, effective measures need to be taken in the preparation of the composite coating to improve the corrosion resistance of the composite coating.

[0108] Erosion performance optimization: The erosion resistance index of the composite coating is compared with the preset erosion resistance threshold to optimize the erosion performance of the composite coating.

[0109] Specifically, the corrosion performance of the composite coating is prepared and optimized, and the specific analysis process is as follows:

[0110] The corrosion resistance index of the composite coating is compared with a preset corrosion resistance threshold, wherein the corrosion resistance threshold can be directly obtained from the corrosion experiment information library. If the corrosion resistance index of the composite coating is greater than or equal to the corrosion resistance threshold, there is no need to prepare and optimize the corrosion performance of the composite coating.

[0111] If the corrosion resistance index of the composite coating is less than the corrosion resistance threshold, the composite coating material to be tested is obtained again, and a paint layer is prepared for the composite coating material to be tested. The prepared composite coating material to be tested is recorded as a composite coating, and the composite coating is subjected to corrosion test operation again until the corrosion resistance index of the composite coating is greater than or equal to the preset corrosion resistance threshold for comparison, thereby completing the corrosion performance preparation optimization of the composite coating.

[0112] The above-mentioned operations of preparing the paint layer again and testing are different from the original operations in that: graphene and other nanomaterials are introduced into the composite coating to enhance the performance of the composite coating; the sol-gel method is used to prepare a composite coating with a dense structure and strong adhesion; the raw materials are strictly screened to ensure that their quality and performance meet the requirements; the test process is strictly controlled to avoid the influence of human factors on the corrosion resistance of the composite coating, so as to obtain a composite coating with the best corrosion resistance.

[0113] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the present invention, they should all fall within the protection scope of the present invention.

Claims

1. A composite coating erosion simulation test method, characterized in that: include: Composite coating preparation: obtaining a composite coating material to be tested, preparing a paint layer for the composite coating material to be tested, and recording the prepared composite coating material to be tested as a composite coating; Evaluation of corrosion resistance performance index: salt spray test method, wet heat test method and electrochemical corrosion test method are used to carry out corrosion test operation on the composite coating respectively, and the corrosion resistance performance index of the composite coating is comprehensively evaluated; Erosion performance optimization: The erosion resistance index of the composite coating is compared with the preset erosion resistance threshold to optimize the erosion performance of the composite coating; The corrosion resistance index of the composite coating is obtained by performing corrosion experiments on the composite coating through salt spray test, wet heat test and electrochemical corrosion test, respectively, to obtain the corrosion degree of the composite coating in the salt spray test, the corrosion degree of the composite coating in the wet heat test and the corrosion degree of the composite coating in the electrochemical corrosion test, and comprehensively analyzing the corrosion resistance index of the composite coating. The specific analysis formula is: θ=[ln(2+Y*y1+S*y2+F*y3)] -1 ; Wherein θ represents the corrosion resistance index of the composite coating, Y represents the corrosion degree of the composite coating in the salt spray test, S represents the corrosion degree of the composite coating in the wet heat test, F represents the corrosion degree of the composite coating in the electrochemical corrosion test, y1 represents the weight factor corresponding to the corrosion degree of the composite coating in the salt spray test predefined in the corrosion test information library, y2 represents the weight factor corresponding to the corrosion degree of the composite coating in the wet heat test predefined in the corrosion test information library, and y3 represents the weight factor corresponding to the corrosion degree of the composite coating in the electrochemical corrosion predefined in the corrosion test information library; The electrochemical corrosion test method includes electrolyte, saturated calomel electrode and electrolytic cell. The composite coating is used as a working electrode, and a saturated calomel electrode is used as a reference electrode, and they are placed together in an electrolytic cell, and an electrolyte is added to form an electrochemical cell; By conducting an electrochemical corrosion test on the composite coating, the electrochemical data of electrochemical corrosion is obtained, and the erosion degree of the electrochemical corrosion composite coating is evaluated; The specific analysis process of the electrochemical corrosion composite coating erosion degree is as follows: According to the electrochemical data of electrochemical corrosion, the current and potential of the electrochemical cell at each corrosion time point are extracted, and the current-potential change curve in the electrochemical cell is constructed, from which the maximum polarization resistance of the electrochemical cell during the corrosion cycle is extracted; Obtaining the adhesion between the composite coating and the substrate at the corrosion termination time point, the environmental initial temperature of the electrochemical corrosion test area at the corrosion start time point, and the environmental temperature of the electrochemical corrosion test area at the corrosion termination time point; The influence factors corresponding to the unit value of polarization resistance, defined adhesion and reference temperature difference are extracted from the corrosion experiment information database, and the corrosion degree of electrochemical corrosion composite coating is comprehensively analyzed. The specific expression is: Where ΔW = (CW-HW)*b1; Wherein F represents the corrosion degree of the electrochemical corrosion composite coating, Z represents the maximum polarization resistance of the electrochemical cell during the corrosion cycle, N represents the adhesion between the composite coating and the substrate at the corrosion termination time point, N' represents the defined adhesion, ΔW represents the ambient temperature difference in the electrochemical corrosion test area, W' represents the reference temperature difference, a1 represents the influence factor corresponding to the unit value of the polarization resistance defined in the corrosion experiment information library predefined in the corrosion experiment information library, a2 represents the influence factor corresponding to the unit value of the corrosion degree of the electrochemical corrosion composite coating predefined in the corrosion experiment information library, CW represents the initial ambient temperature of the electrochemical corrosion test area at the corrosion start time point, HW represents the ambient temperature of the electrochemical corrosion test area at the corrosion termination time point, b1 represents the influence factor corresponding to the unit value of the temperature difference predefined in the corrosion experiment information library, and e is a natural constant.

2. The method for simulating the corrosion of a composite coating according to claim 1, characterized in that: The erosion performance of the composite coating is prepared and optimized, and the specific analysis process is as follows: Comparing the erosion resistance index of the composite coating with a preset erosion resistance threshold, if the erosion resistance index of the composite coating is greater than or equal to the erosion resistance threshold, there is no need to prepare and optimize the erosion performance of the composite coating; If the corrosion resistance index of the composite coating is less than the corrosion resistance threshold, the composite coating material to be tested is obtained again, and a paint layer is prepared for the composite coating material to be tested. The prepared composite coating material to be tested is recorded as a composite coating, and the composite coating is subjected to corrosive experimental operation again until the corrosion resistance index of the composite coating is greater than or equal to the preset corrosion resistance threshold, thereby completing the corrosion performance preparation optimization of the composite coating.

3. The method for simulating the corrosion of a composite coating according to claim 1, characterized in that: The salt spray test method includes salt spray test box, edible salt, distilled water and ethanol. The salt spray test data is obtained by subjecting the composite coating to a salt spray test, and the corrosion degree of the composite coating in the salt spray test is obtained by evaluation.

4. The method for simulating the corrosion of a composite coating according to claim 3, characterized in that: The specific analysis process of the salt spray test composite coating corrosion degree is as follows: According to the salt spray test data, the initial pH value in the salt spray test chamber, the pH value of the salt spray test chamber at the end time of the test, and the number of bubbles on the surface of the composite coating are extracted; The initial pH value in the salt spray test chamber is processed with the pH value of the salt spray test chamber at the end time of the test to obtain the pH change value of the salt spray test chamber during the test period; The initial salt spray concentration in the salt spray test area and the salt spray concentration in the salt spray test area at the test termination time point are obtained, and ratio processing is performed to obtain the environmental salt spray leakage degree of the salt spray test within the test period, and multiplied by the correction factor corresponding to the environmental salt spray leakage degree to obtain the salt spray test environmental salt spray leakage impact index; Extract the correction factors corresponding to the acid-base reference change value and the environmental salt spray leakage from the corrosion test information database; The acid-base change value of the salt spray test box during the test period is processed by ratio with the acid-base reference change value to obtain the acid-base change index of the salt spray test box; The number of bubbles on the composite coating surface is multiplied by the impact factor corresponding to a single bubble to obtain the erosion impact index of the composite coating surface; The salt spray leakage impact index of the salt spray test environment, the acid-base change index of the salt spray test box and the corrosion impact index of the composite coating surface are added together to obtain the corrosion degree of the composite coating in the salt spray test.

5. The method for simulating the corrosion of a composite coating according to claim 1, characterized in that: The damp heat test method, the specific material is a high and low temperature damp heat test box; By carrying out a wet heat test on the composite coating, a data set of the wet heat test is obtained, thereby evaluating the corrosion degree of the composite coating in the wet heat test.

6. The method for simulating the corrosion of a composite coating according to claim 5, characterized in that: The specific analysis process of the wet heat test composite coating erosion degree is as follows: According to the data set of the wet heat test, the peeling area of ​​the composite coating at the wet heat termination time point, the total area of ​​the composite coating, the initial coating thickness of the composite coating, and the coating thickness of the composite coating at the wet heat termination time point are extracted; The erosion and spalling ratio of the composite coating is obtained by performing a ratio processing of the spalling area of ​​the composite coating at the end time point of the wet heat treatment to the total area of ​​the composite coating; The initial coating thickness of the composite coating and the coating thickness of the composite coating at the end time point of the wet heat treatment are subjected to difference processing to obtain the coating thickness difference of the composite coating during the wet heat treatment cycle, and the difference is multiplied by the influence factor corresponding to the coating thickness difference to obtain a value recorded as the erosion thickness influence value of the composite coating; The erosion and spalling ratio of the composite coating is processed by ratio processing with the erosion and spalling limit ratio defined in the erosion experiment information database to obtain the erosion and spalling index of the composite coating; The erosion thickness influence value of the composite coating and the erosion spalling index of the composite coating are added together to obtain the erosion degree of the composite coating in the wet heat test.

7. The method for simulating the corrosion of a composite coating according to claim 1, characterized in that: The paint layer of the composite coating material to be tested is prepared, and the specific analysis process is as follows: According to the composite coating material to be tested, it specifically includes isobutyl triethoxysilane, water, cement, machine-made sand, rubber powder, nano silicon dioxide, admixtures and sodium laurate; Preparing a paint layer on the composite coating material, wherein the paint layer preparation includes preparing a composite coating primer, preparing a composite coating intermediate paint, and preparing a composite coating topcoat; The composite coating primer is prepared by adding isobutyl triethoxysilane to water, wherein the ratio of the volume of isobutyl triethoxysilane to the volume of water is the same as a preset ratio, thereby obtaining the composite coating primer; The composite coating intermediate paint is prepared by mixing cement, machine-made sand, rubber powder and nano-silicon dioxide according to a preset ratio, stirring for a first specified time to obtain a dry material mixture, adding water and an admixture to the dry material mixture, stirring for a second specified time to obtain a composite coating intermediate paint; The composite coating topcoat is prepared by adding sodium laurate to water and stirring for a third specified time to obtain the composite coating topcoat; The paint layer of the composite coating material is prepared according to the composite coating primer, the composite coating intermediate paint and the composite coating topcoat, and the prepared composite coating material to be tested is recorded as a composite coating.

Citation Information

Patent Citations

  • A penetrating protective agent for improving the durability and apparent quality of hydraulic concrete

    CN104693967B

  • A durable protective coating for concrete surfaces

    CN116589907B

  • Simulated accelerated corrosion testing method of ship fastener and protective coating

    CN102621058A